2007
DOI: 10.1002/cphc.200700331
|View full text |Cite
|
Sign up to set email alerts
|

57Fe Mössbauer Spectroscopy and Electron Microscopy Study of Metal Extraction from CuFe2O4 Electrodes in Lithium Cells

Abstract: Active CuFe(2)O(4) electrode materials for lithium cells are produced by thermal decomposition of a citrate precursor. The precipitation of the metal citrate is carried out by a freeze-drying procedure. A tetragonally distorted spinel structure is prepared by the decomposition of a citrate precursor. Samples free of impurities are obtained depending on the annealing temperature. The sample heated at 800 degrees C performed at 470 mAh g(-1) after 50 cycles. Electron microscopy is used as the ultimate technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 29 publications
(39 reference statements)
0
39
0
Order By: Relevance
“…Initially, the unexpected reversibility of the conversion process was reported for binary first-row transition metal oxides, while subsequently it was extended to mixed oxides [5][6][7][8][9][10][11][12]. More recently, we were able to extend the reversible conversion to transition metal oxysalts, such as oxalates and carbonates, in which new mechanisms of charge storage such as double layer capacitive effects were detected [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 91%
“…Initially, the unexpected reversibility of the conversion process was reported for binary first-row transition metal oxides, while subsequently it was extended to mixed oxides [5][6][7][8][9][10][11][12]. More recently, we were able to extend the reversible conversion to transition metal oxysalts, such as oxalates and carbonates, in which new mechanisms of charge storage such as double layer capacitive effects were detected [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 91%
“…Several oxide systems containing two transition metals and crystallizing in a spinel structure have been studied to date, namely, MMn 2 O 4 (M = Co [ 43 ] ), MFe 2 O 4 (M = Co, [ 282 , 289,290 ] Ni, [ 290 , 291 ] Cu [ 292 ] ), and MCo 2 O 4 (M = Mn, [ 43 ] Fe, [ 282 , 293 ] Ni, [ 294 , 295 ] Cu [ 296 ] ), which show an overall performance that is similar to that of simple oxides. It is interesting to note that in all the cases reported so far the signature of their reduction is, systematically, a single plateau instead of the two that could be expected from the different potentials at which the individual oxides react, suggesting that the occurrence of mixed states at the Fermi level results in simultaneous reduction to the metallic state.…”
Section: Mixed Transition Metal Compoundsmentioning
confidence: 99%
“…Firstly, Chen and Greenblatt [8] have reported that the transition metal ferrites with spinel structure used for cathode materials for Li-ion batteries. Spinel-type ferrite anodes, like NiFe 2 O 4 [9], CuFe 2 O 4 [10], CoFe 2 O 4 [11], ZnFe 2 O 4 [2] and CaFe 2 O 4 [12] have gained in significance due to their high specific capacities and simplistic synthesis. The higher capacity observed for the latter materials (i.e.…”
Section: Introductionmentioning
confidence: 99%